2009
DOI: 10.1515/integ.2009.023
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Expansions with Negative Bases

Abstract: This paper investigates representations of real numbers with an arbitrary negative base ˇ< 1, which we call the . ˇ/-expansions. They arise from the orbits of the . ˇ/-transformation which is a natural modification of theˇ-transformation. We show some fundamental properties of . ˇ/-expansions, each of which corresponds to a well-known fact of ordinaryˇ-expansions. In particular, we characterize the admissible sequences of . ˇ/-expansions, give a necessary and sufficient condition for the . ˇ/-shift to be sofic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 10 publications
1
102
0
Order By: Relevance
“…The (−β)-expansions, a numeration system built in analogy with Rényi βexpansions, was introduced in 2009 by Ito and Sadahiro (see [8]). They gave an alternate-lexicographic criterion for deciding whether some digit string is the (−β)expansion of some x and also described some properties of the corresponding (−β)shift, which was also subject of [2], [3] and [7].…”
Section: Numeration With Negative Basementioning
confidence: 99%
“…The (−β)-expansions, a numeration system built in analogy with Rényi βexpansions, was introduced in 2009 by Ito and Sadahiro (see [8]). They gave an alternate-lexicographic criterion for deciding whether some digit string is the (−β)expansion of some x and also described some properties of the corresponding (−β)shift, which was also subject of [2], [3] and [7].…”
Section: Numeration With Negative Basementioning
confidence: 99%
“…Recent results in theoretical computer science have shown that negative β-expansions, i.e., expansions of the form x = ∞ k=1 (b k /(−β) k ), have better robustness properties when used for encoding purposes [AHK08]. In [IS09] Ito and Sadahiro studied 154…”
Section: Introductionmentioning
confidence: 99%
“…Piecewise linear expanding interval maps with constant negative slope in general and the map S I S in particular have also generated a lot of attention. The papers [DK11,Gór09,Hof12,IS09,LS12] deal, among other things, with invariant measures, transitivity and attractors of the maps in question. It seems natural to ask exactly how different the positive and negative slope maps really are.…”
Section: Introductionmentioning
confidence: 99%
“…This changed only in recent years, after Ito and Sadahiro [IS09] , i.e., b n = ε n (x) for all n ≥ 1. Since the map x → −βx is order-reversing, the (−β)-admissible sequences are characterized using the alternating lexicographic order.…”
mentioning
confidence: 99%
“…Since the map x → −βx is order-reversing, the (−β)-admissible sequences are characterized using the alternating lexicographic order. By [IS09], a sequence b 1 b 2 · · · is (−β)-admissible if and only if…”
mentioning
confidence: 99%